2003
DOI: 10.1007/s00432-002-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in matrix metalloproteinases and their endogenous inhibitors during tumor progression in the uterine cervix

Abstract: Purpose: To study the role of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in cervical tumorigenesis, we analyzed 70 cervical tissue specimens that included 15 low-grade squamous intraepithelial lesions (SILs), 20 high-grade SILs, 25 squamous cell carcinomas (SCCs) and 10 specimens of normal cervical tissue. Methods: The gelatinolytic activity of MMP-9 and MMP-2 was determined by zymographic analysis. The expression of MMP-9 and MMP-2 and TIMP-1 and TIMP-2 was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…Our observation was also supported by the findings of Asha Nair et al . which reported that TIMP-2 levels were increased during tumor progression in the uterine cervix [33]. However our results are in contrast with Branca et al that demonstrated down regulation of TIMP-2 in invasive cervical carcinomas [34].…”
Section: Discussioncontrasting
confidence: 99%
“…Our observation was also supported by the findings of Asha Nair et al . which reported that TIMP-2 levels were increased during tumor progression in the uterine cervix [33]. However our results are in contrast with Branca et al that demonstrated down regulation of TIMP-2 in invasive cervical carcinomas [34].…”
Section: Discussioncontrasting
confidence: 99%
“…High expression of MMP‐2 in human cervical carcinoma cell lines have also been associated with presence of HPV (13). MMP‐2 expression has been shown to gradually increase according to the degree of cervical intraepithelial neoplasia (CIN) and cervical carcinoma (14–18). Increased MMP‐9 mRNA and protein expression was found in high grade CIN and squamous cell cervical invasive carcinoma suggesting MMP‐9 to be an early marker of tumor progression (19).…”
Section: Discussionmentioning
confidence: 99%
“…Increased MMP‐9 mRNA and protein expression was found in high grade CIN and squamous cell cervical invasive carcinoma suggesting MMP‐9 to be an early marker of tumor progression (19). High grade cervical squamous intraepithelial lesions (SIL) and squamous cell carcinomas showed intense cellular and stromal reactivity for MMP‐9 when compared to low‐grade cervical SILs and normal cervical epithelium (14). Both vulvar and cervical squamous cell carcinoma are known to develop through premalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Many extracellular proteases have been demonstrated to directly activate MMPs including other MMPs (e.g., MMP-3 activation of the MMP-9 [11]) and non-MMP proteins (e.g., plasmin activation of MMP-3 [12]). High levels of metalloproteinases, especially MMP-2 and/or MMP-9 have been demonstrated in many cancers, including pancreatic [13–20], breast [21], cervical [22], and ovarian cancer [23]. Similarly, the human kallikrein-related peptidases constitute an important group of serine proteases that are up-regulated in various cancers (reviewed in [24–25]).…”
Section: Introductionmentioning
confidence: 99%